AB0369 Comparative Effectiveness Abatacept, Adalimumab and Rituximab in Patients with Long-Standing Rheumatoid Arthritis in A Real-Life Setting. (15th July 2016) - Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; Cardozo, A.; Palacio, N.; Castro, C.; et al.
Abstract : Background: Clinical response in patients with rheumatoid arthritis (RA) using biologics is well-known. However, there is no direct comparison between biologics in cohorts of patients with long-standing RA in real-life settings, which could have implications in treatment decisions and health economics. Objectives: The aim of this study was to describe a direct comparison in effectiveness between three different biological agents in their mechanism of action and its application in patients with long-standing RA in a cohort of real-life. Methods: A descriptive retrospective study was performed. Were included 242 patients with at least 12 visits to rheumatologist in last 24 months. Clinical follow-up was according to DAS28: every 3–5 weeks (DAS28 >5.1), every 7–9 weeks (DAS28 ≥3.1 and ≤5.1), and every 11–13 weeks (DAS28 <3.1). Therapy had to be adjusted with DAS28 >3.2 unless patient's conditions don't permit it. We divided patients in two groups: remission-low disease activity (Rem/LDA) patients and moderate-severe disease activity (MDA/SDA) patients and the aim of the study was to analyze of patients who were in MDA/SDA disease activity how many reached a Rem/LDA status. Patients with diagnosis of RA and using Abatacept, Adalimumab and Rituximab were involved. Descriptive epidemiology was done, percentages and averages were calculated; the median of each variable was analyzed using t-Student assuming normality for DAS28 distribution and the level activity disease was analyzed using Pearson's statistics. Results: 242 patients were included, 201 (83%) women and 41 (17%) men. Mean age was 58±10 years; patients with RA and using Abatacept, Adalimumab and Rituximab were involved and treatments were distributed as follows: Abatacept 72 (30%), Adalimumab 96 (40%) and Rituximab 74 (30%); At 24 months was observed an increase in percentage of patients in Rem/LDA and a decrease in percentage of patients in MDA/SDA disease activity statistically significant. For Abatacept at beginning the mean DAS28–3.8 and 24 months later DAS28–2.7; for Adalimumab at beginning the mean DAS28–3.2 and 24 months later DAS28–2.6; for Rituximab at beginning the mean DAS28–3.7 and 24 months later DAS28–2.5; although the HAQ reduction had clinical relevance there was no statistically significance. Between these biologics were not differences statistically significant in effectiveness. A very important issue was that at the end of the follow-up there was no patients in severe disease activity. Conclusions: Study shows no significant differences in effectiveness between three different biological agents in their mechanism of action and its application analyzed, but there was a clear improvement in all patients with respect to basal disease activity, which proves effectiveness of implementation of a T2T strategy in patients with long-standing RA independent of biological. Disclosure of Interest: None declared